The Societal Role of Evangelical Lutheran Parishes in Rural Finland. (1st January 2013) - Pesonen, Heikki; Niska, Miira; Vesala, Kari Mikko
Abstract: Since the 1980s rural policies have emphasized the importance of public, private and voluntary sector partnerships. Although actors from all sectors are encouraged to join rural development work, the participation of religious communities has been a controversial issue. This article focuses on the role of religious communities in rural development policy in Finland: how the representatives of the Evangelical-Lutheran parishes and other rural actors see the role of the Church and parishes in secular rural development work. The study is based on qualitative interview data gathered from four Finnish rural parishes, combining qualitative attitude approach and frame analysis. The results indicate that, although reservations were also presented, the participation of parishes in rural development work was often considered desirable and feasible, both by the parish representatives and other local actors. This positive attitude, however, appeared to depend on flexibility in how the religious frame and the frame of rural development were evaluated, used and reconciled. The complexities of framing and reframing of parish participation in rural development reflect the more general challenge for the Church to maintain and renew its role and position in secularizing society.